Gerakan Perempuan LSM dalam Sastra Indonesia: Evidensi pada Novel Perempuan yang Menangis Kepada Bulan Hitam Karya Dian Purnomo - Ahmad Burhanuddin; Anas Ahmadi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Women experience domestic violence, workplace harassment and sexual violence in various parts of the world. The current global situation is encouraging violence against women to increase. The issue of violence against women has attracted the attention of various organizations, including Non-Governmental Organizations (NGOs). In the novel Perempuan yang Menangis kepada Bulan Hitam, there is an NGO called Gema Perempuan which helps many women victims of violence resolve their cases. This research will discuss the role of Gema Perempuan in the novel. This research is qualitative. The data collection technique in this research is a library technique. The data analysis technique in this research uses content analysis techniques. From the study, it was found that the various roles of protecting victims by Gema Perempuan in the novel include: 1) providing moral support to the victims to keep them enthusiastic, 2) giving advice to the victims about what they should do to get out of a detrimental situation, 3) Assistance to victims by providing temporary shelter, and 4) providing training to various parties who support the protection of women. The role of Gema Perempuan as seen in the novel can represent a role that is not much different from women's protection NGOs in the real world. This shows that women's protection NGOs play an important role in their social function, namely protecting women